Sykes–Picot-egyezmény: az “arabság trianonja”? SYKES–PICOT-AGREEMENT: “TRIANON OF THE ARABS”? - Rostoványi , Zsolt (Közép-Európai Közlemények, 2020)
The Ottoman Empire fought in the First World War on the side of the Central Powers, which accelerated the disintegration of the Empire. The “Eastern question,” that is, the imperial/colonial competition of great powers for the lost territories of the Empire have already been an integral part of European power politics for decades. On May 19, 1916 Great Britain, France and Russia have concluded the Sykes-Picot Agreement that divided the “Fertile Crescent” region into British and French spheres of interest. In return for a military uprising of Arab forces (“Arab Revolt”) against the Ottoman Sultan led by Hussein, Sharif of Mecca, the British promised support for an independent Arab state. However, Arab expectations proved futile. From 1923, the League of Nations mandates came into force in the form of four new states: Syria-Lebanon became French, Palestine, Trans-Jordan and Iraq became British mandates. Although the actual country borders were not designated by the Sykes-Picot Agreement, this treaty has become the symbol of colonization, of imperialist politics, of “artificial state borders" drawn by the West, and of “artifical states” created from territories divided up by imperialist powers.